Atividade antibacteriana de derivados do lapachol e norlapachol e avalição da inibição de bombas de efluxos em linhagens de Staphylococcus aureus - Figueredo, Fernando Gomes (2022)
Isolated substances and those organically synthesized have stood out over the years for their therapeutic properties, including their antibacterial activity. In this context, the aim of this research was to investigate the pharmacological properties of 2-(2 hydroxyethylamine)-3-(3-methyl-2-butenyl)-1,4-dihydro-1,4-naphthalenedione, 2-(2- hydroxy-ethylamine)-3-(2-methyl-propenyl)-[1,4] naphthoquinone and 2-(3-hydroxypropylamine)-3-(3-methyl-2-butenyl)-[1,4]naphthoquinone using computational prediction models, to evaluating the in vitro antibacterial and modulatory activity of these compounds against bacterial ATCC strains and clinical isolates, in addition to analyzing the inhibitory effect on the efflux pump functioning of these substances in strains of multiresistant Staphylococcus aureus. The substances were synthesized from 2-hydroxyquinones, lapachol and nor-lapachol obtaining the corresponding 2-methoxylated derivatives via dimethyl sulfate alkylation in a basic medium, these then reacted chemoselectively with 2-ethanolamine and 3-propanolamine to form the corresponding amino alcohols. The antibacterial activity and modulatory activity of the substances were assayed by broth microdilution method to determine the Minimum Inhibitory Concentration (MIC). To verify the effect of reducing the MIC of the ethidium bromide and the antibiotic, inoculums obtained from plates incubated in a bacteriological oven for 24 hours at 37ºC with the stock peaking were used. After this period inoculums were used in saline solution according to Mcfarland 0.5 corresponding to 105UFC. The results of the tests were done in triplicates and as geometric mean. In the statistical analysis, oneway ANOVA was used, followed by the Tukey hoc post test using GraphPad Prism 5.0.The molecular structures were analyzed using the ChEMBL database to predict possible pharmacological targets and soon after underwent a virtual structure-based analysis (docking)., which pointed to the molecule 2- (2-hydroxy-ethylamine)-3-(2-methyl-propenyl)-[1,4]naphthoquinone as a probable antibacterial agent for the proteins Replicative DNA helicase and RecA. The MICs of the substances were not clinically significant, however, the association with gentamicin and amikacin reduced the MICs of these antibiotics with significance of p < 0.0001. against Staphylococcus aureus strains carrying the NorA efflux pump mechanism, a significant reduction (p < 0,0001) of their MICs was observed when the substances were associated with norfloxacin and ethidium bromide, with this effect being attributed to efflux pump inhibition. Following a virtual analysis based on its structure (docking), information regarding the affinity of new ligands for the ABC efflux pump. The tested substances also demonstrated effectiveness at decreasing the MIC of erythromycin, tetracycline and mainly of ethidium bromide with MIC reduction up to 16x. In conclusion, the combination of these substances with antibiotics may be a therapeutic alternative to bacterial resistance and the reduction of side effects.